Hubungan Frekuensi Konsumsi Minuman Berpemanis Dengan Kejadian Gizi Lebih Pada Remaja SMP Negeri 28 Surabaya - Anli Manuela; Noor Rohmah Mayasari (PT. Gudang Pustaka Cendekia, 2026)
The consumption of sugar-sweetened beverages (SSBs) among adolescents has increased and may contribute to the rising prevalence of overweight due to their high sugar and energy content. This study aimed to analyze the relationship between the consumption of sugar-sweetened beverages and the incidence of overweight among adolescents at SMP Negeri 28 Surabaya. This study employed an analytical observational design with a cross-sectional approach. A total of 164 respondents were selected using proportional random sampling. Data on sugar-sweetened beverage consumption were collected using a Food Frequency Questionnaire (FFQ), while nutritional status was assessed using Body Mass Index-for-Age (BMI-for-Age). Data were analyzed using the Chi-square test. The results showed a significant association between the consumption of sweetened tea (p = 0.023) and carbonated soft drinks (p = 0.000) with overweight, whereas the consumption of coffee, bubble tea, sweetened milk, isotonic drinks, syrup, and yogurt was not significantly associated with overweight (p > 0.05). It can be concluded that frequent consumption of sweetened tea and carbonated soft drinks is associated with an increased risk of overweight among adolescents. Therefore, nutrition education and limiting the consumption of sugar-sweetened beverages are recommended as preventive strategies to reduce overweight among adolescents.